2014
DOI: 10.1016/j.ejvs.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Infections of Intravascular Bare Metal Stents: A Case Report and Review of Literature

Abstract: Intravascular stent infection is associated with a high risk of morbidity and mortality. Surgery is the preferred treatment option, but not always possible, especially in patients with a coronary stent. In selected cases, bare metal stent infections may be prevented by the use of prophylactic antibiotics at stent placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
106
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 78 publications
0
106
0
Order By: Relevance
“…[4]. Common organisms cultured in endovascular device infections were noted to be Staphylococcus aureus at 54.4% [3,4]. Furthermore, Fiorini et al, found that Staphylococcus aureus accounted for 70% of early infections and 30% of later diagnosed infections [5].…”
Section: Literature Review/discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4]. Common organisms cultured in endovascular device infections were noted to be Staphylococcus aureus at 54.4% [3,4]. Furthermore, Fiorini et al, found that Staphylococcus aureus accounted for 70% of early infections and 30% of later diagnosed infections [5].…”
Section: Literature Review/discussionmentioning
confidence: 99%
“…Furthermore, Fiorini et al, found that Staphylococcus aureus accounted for 70% of early infections and 30% of later diagnosed infections [5]. Bosman et al discovered that 76.6% of infected endovascular devices were caused by Staphylococcus aureus [4]. Lichtenfels et al suggest the main factors associated with development of infection in endovascular devices are found with immunodepression, specific site of endovascular procedure, previous pseudo and mycotic aneurysms, presence of neoplasm, and use of corticosteroids [6,7].…”
Section: Literature Review/discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes and smoking independently increase the infection risk; however, other risk factors previously reported for endovascular procedures, such as absence of sterility, lack of antibiotic prophylaxis, introducer sheath permanence more than 24 h, multiple stents implantation, or multiple procedures in the same region [3], were not present in our case. Infected stent and/or stent-graft usually appear as device thrombosis, septic embolization, pseudoaneurysm, and hemorrhage [10]. Schneider et al [3] reported a single case of SFA autolysis after Viabahn stent-graft implantation for SFA atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 99%